Testing of Software and Communication Systems 21st IFIP WG 6.1 International Conference, TESTCOM 2009 and 9th International Workshop, FATES 2009, Eindhoven, The Netherlands, November 2-4, 2009, Proceedings - Nunez, Manuel; Baker, Paul; Merayo, Mercedes G. (Computer Communication Networks and Telecommunications, 2009)
This book constitutes the refereed proceedings of the 21th IFIP WG 6.1 International Conference on Testing Communicating Systems, TESTCOM 2009, and the 9th International Workshop on Formal Approaches to Testing of Software, FATES 2009, jointly held in Eindhoven, The Netherlands, in November 2009. The 13 revised full papers presented together with 6 short papers were carefully selected from 37 submissions to both events. The papers cover new approaches, concepts, theories, methodologies, tools, and experiences in the field of testing of communicating systems and general software.